Cultural Influences on Risk Tolerance: Evidence for Students in Indonesia - Wiryono, Sudarso Kaderi; Kitri, Mandra Lazuardi; Novani, Santi; Belgiawan, Prawira Fajarindra; Setiawati, Marla (International Review of Management and Marketing, 2020)
This paper examined the impact of culture on risk tolerance for students in Indonesia. By using surveys that had been completed by 309 college students, this research used logistic regression as the main method. This research found that there is no evidence that Western Indonesia would score as more risk-tolerant on standard risk assessment questionnaire and would choose portfolio allocations that are riskier than Central & Eastern Indonesia. Parents' higher education has given a significant result to the risk tolerance match. The theoretical and practical implications of this research are discussed. Our findings suggest that differences in risk tolerance are at least partially a product of a culture which is a tribe in each region, but such differences may not always be reflected in actual investment decisions. Keywords: Risk tolerance, cultural influences, tribe JEL Classifications: I0, Z0 DOI: https://doi.org/10.32479/irmm.10224